Language, power, and media intimidation: a Foucauldian discourse analysis - Fensi, Fabianus (Jurnal Studi Komunikasi, 2025)
This article analysed the controversial public statement made by political consultant Hasan Nasbi, “just cook the pig’s head”, in response to an act of symbolic intimidation toward a journalist. Using Michel Foucault’s discourse theory as the primary analytical framework—focusing on statement analysis, historical context, and power relations—this study investigates how language operates as a mechanism of power that normalises symbolic violence, marginalises dissent, and sustains hegemonic authority. The findings show that Nasbi’s language is not merely rhetorical but functions ideologically: it delegitimises journalistic victimhood, redefines social norms of seriousness and threat, and enacts a regime of truth that reinforces the asymmetry of power in public discourse. Drawing from contemporary discourse studies, the study argues that such statements reproduce a surveillance-based form of control, wherein symbolic aggression is trivialised, and political accountability is eroded. This research contributes to the growing field of critical discourse analysis by demonstrating how everyday political utterances carry deep ideological functions and shape the boundaries of public meaning, legitimacy, and justice.